2006
DOI: 10.1086/498518
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Staphylococcus aureus from the Urinary Tract: Association of Isolation with Symptomatic Urinary Tract Infection and Subsequent Staphylococcal Bacteremia

Abstract: S. aureus is a cause of urinary tract infection among patients with urinary tract catheterization. The majority of isolates are methicillin-resistant S. aureus. S. aureus bacteriuria can lead to subsequent invasive infection. The efficacy of antistaphylococcal therapy in preventing late-onset staphylococcal infection in patients with persistent staphylococcal bacteriuria should be tested in controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
132
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 29 publications
(24 reference statements)
10
132
2
1
Order By: Relevance
“…Fowler et al 7 proposed a prognostic model of complicated SAB using the predictors from their study; community acquisition of organisms, persistent bacteremia, persistent fever over 72 hours, and skin examination suggestive of an acute systemic infection. Muder et al 8 reported a relationship between SABU and subsequent SAB, but they did not examine the association between SABU and the risk of complicated SAB. Huggan et al 9 found that concomitant SABU is associated with ICU admission and increased in-hospital mortality in patients with SAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fowler et al 7 proposed a prognostic model of complicated SAB using the predictors from their study; community acquisition of organisms, persistent bacteremia, persistent fever over 72 hours, and skin examination suggestive of an acute systemic infection. Muder et al 8 reported a relationship between SABU and subsequent SAB, but they did not examine the association between SABU and the risk of complicated SAB. Huggan et al 9 found that concomitant SABU is associated with ICU admission and increased in-hospital mortality in patients with SAB.…”
Section: Discussionmentioning
confidence: 99%
“…Fowler et al 7 postulated some clinical identifiers of complicated SAB; however, predicting which patients will develop a complication from SAB remains very difficult. Muder et al 8 demonstrated that the presence of SA bacteriuria (SABU) correlates with subsequent SAB, but a possible association of SABU with complicated bacteremia was not examined. A more recent study from Huggan et al 9 has suggested a possible association between SABU and poor clinical outcomes in adults with SAB.…”
mentioning
confidence: 99%
“…However, recent epidemiologic studies indicate that S. aureus is an emerging cause of UTI in special patient populations, such as pregnant women and those with complicated UTI (4)(5)(6)(7)(8)(9)(10). Complicated S. aureus UTIs are predominately associated with the presence of foreign bodies (i.e., urinary catheters or kidney stones) (4,9,11,12), recent hospital exposure (8), residence in a long-term care facility (6,13), and other comorbidities such as prostatic abscesses following prostatitis, diabetes, and cancer (14,15). Of particular concern, complicated S. aureus UTIs are frequently associated with the development of severe sequelae, leading to increased rates of morbidity and mortality (4,6,8,12,13,(16)(17)(18).…”
mentioning
confidence: 99%
“…Complicated S. aureus UTIs are predominately associated with the presence of foreign bodies (i.e., urinary catheters or kidney stones) (4,9,11,12), recent hospital exposure (8), residence in a long-term care facility (6,13), and other comorbidities such as prostatic abscesses following prostatitis, diabetes, and cancer (14,15). Of particular concern, complicated S. aureus UTIs are frequently associated with the development of severe sequelae, leading to increased rates of morbidity and mortality (4,6,8,12,13,(16)(17)(18). Additionally, treatment of these infections has become increasingly difficult, as most S. aureus isolates causing complicated UTI are methicillinresistant S. aureus (MRSA) and are refractory to treatment by antibiotics that typically have efficacy in the urinary tract (4,8,12,19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation